'No objection to go abroad': Servants' Travel Advertisements in The Morning Post, London, 1815. (11th August 2022) - Dunn, Sophie
Abstract: This article focuses on newspaper advertisements posted by, or on behalf of, servants who were offering their services to travellers to the European continent at the end of the long eighteenth century. Advertising their travel‐related skills, such as languages or knowledge of the roads, travelling servants positioned themselves as ideal travel companions who anticipated their employers' needs and used their skills as a self‐marketing strategy to stand out in a competitive job market. These advertisements give us an idea how servants imagined worthwhile employment, what they desired or objected to, and where they were willing to compromise.